Bee Venom and Hesperidin Effectively Mitigate Complete Freund’s Adjuvant-Induced Arthritis Via Immunomodulation and Enhancement of Antioxidant Defense System - Osama AHMED; Hanaa FAHIM; Ayman MAHMOUD; Eman AHMED (Archives of Rheumatology, 2018)
Objectives: This study aims to assess the antirheumatic activity of bee venom (BV) and/or hesperidin as natural products in complete Freund’s adjuvant (CFA)-induced arthritis in male Wistar rats. Material and methods: Rheumatoid arthritis was induced in 30 male Wistar rats (weight 130 g to 150 g; age 10 to 12 weeks) by subcutaneous injection of CFA into the right hind paw of the rats. The rats were divided into five groups of six rats in each and administered the following regimens for 21 days: Normal group (given the equivalent volume of saline and carboxymethylcellulose), arthritic group (given the equivalent volume of saline and carboxymethylcellulose), arthritic group treated with BV (treated with BV along with carboxymethylcellulose), arthritic group treated with hesperidin (treated with hesperidin along with saline), and arthritic group treated with BV and hesperidin (treated with BV and hesperidin concurrently). Results: Bee venom and/or hesperidin successfully reversed the CFA-arthritis-induced increases in right hind leg paw swelling, leukocytes’ count, liver lipid peroxidation, serum inflammatory cytokine interleukin (IL-2 and IL-12) levels and spleen tumor necrosis factor-alpha messenger ribonucleic acid expression. Moreover, the CFA-induced down-regulation in serum IL-10 level and spleen IL-4 messenger ribonucleic acid expression as well as the deterioration in the antioxidant defense system were significantly improved as a result of BV and hesperidin administration. Both treatments also markedly counteracted the severe inflammatory changes and leukocytic infiltration in the periarticular tissue of the ankle joints. In addition, BV and hesperidin obviously amended the lymphoid hyperplasia in white pulps of spleen as well as the widening of the medulla and mononuclear cell infiltration found in thymus. Conclusion: Bee venom and hesperidin administration produced their ameliorative effects on rheumatoid arthritis via their antioxidant, antiinflammatory and immunomodulatory potentials. BV plus hesperidin particularly seemed to be the most potent in improving rheumatoid arthritis in Wistar rats.